THE LOWER STRATUM OF THE SOCIAL HIERARCHY AND ITS SEMANTIC RETHINKING (Philological Studies, 2019)
The article describes the formation of a figurative meaning in the names of the lowest Russian social strata. Polysemy occurs when the nominative meaning ceases to be relevant. The semantics of the portable meaning of the word "serf" includes the semes of two participants in the situation, voluntary lack of freedom, low behavior. The social hierarchy in figurative use is reinterpreted in the higher status of the speaker as the subject of evaluation.
Keywords: Social stratification, inferior social stratum, historicism, transference, metaphor, compatibility, point of view, negative connotations